2020
DOI: 10.1111/and.13808
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin administration and withdrawal affect testicular structure and functions in rats

Abstract: The aim of this prospective experimental study was to investigate the effects of pregabalin (PG) administration and withdrawal on testicular structures and functions in rats. A total of 24 male Wistar rats were divided into two groups (n = 12 each): a control group received normal saline, and PG‐treated group received 62 mg kg‐1 day‐1 PG for 2 months. Half the animals of each group were sacrificed for the collection of blood and testicular samples. The remaining animals were bred for another 2 months without t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that valproic acid can induce tissue pathological damage associated with autophagy by modulating the AMPK/mTOR signaling pathway ( Alsemeh et al, 2022 ). And another type of AEDs Pregabalin can reduce the number of germ cells while increasing the number of interstitial cells, and cause a decrease in the number and diameter of convoluted tubules ( Salem et al, 2020 ). It also induces cell apoptosis, increases caspase-3 expression in the testis ( Shokry et al, 2020 ), upregulates pro-apoptotic genes BAX and p38 MAPK, and downregulates the anti-apoptotic gene BCL2 ( Taha et al, 2020 ).…”
Section: Main Textmentioning
confidence: 99%
“…Studies have shown that valproic acid can induce tissue pathological damage associated with autophagy by modulating the AMPK/mTOR signaling pathway ( Alsemeh et al, 2022 ). And another type of AEDs Pregabalin can reduce the number of germ cells while increasing the number of interstitial cells, and cause a decrease in the number and diameter of convoluted tubules ( Salem et al, 2020 ). It also induces cell apoptosis, increases caspase-3 expression in the testis ( Shokry et al, 2020 ), upregulates pro-apoptotic genes BAX and p38 MAPK, and downregulates the anti-apoptotic gene BCL2 ( Taha et al, 2020 ).…”
Section: Main Textmentioning
confidence: 99%